Screen-printed wearable skin surface pH sensor for real-time monitoring of the buffering capacity of human skin - Chiba, Kentaro; Harada, Yutaro; Matsumoto, Hirotaka; Matsui, Hiroyuki; Ito, Naoya; Sekine, Tomohito; Nagamine, Kuniaki (Analytical and bioanalytical chemistry, 2024)
This study demonstrated for the first time that skin surface pH can be monitored in real-time, using a screen-printed wearable pH sensor, to evaluate the buffering capacity of the human skin. The screen-printed pH sensor was composed of a polyaniline-based pH-sensitive electrode and a nitrocellulose membrane-based liquid junction type of Ag/AgCl reference electrode. This sensor showed a reliable and reversible potentiometric response to pH with long-term potential stability. Intermittent monitoring of the buffering capacity of skin surface pH demonstrated the reliability of the proposed wearable pH sensor, which was comparable to that of a commercially available flat-tip pH sensor. We found that contact of the wearable pH sensor with the subject’s skin via aqueous electrolyte solutions was necessary for the sensor to continuously monitor the skin surface pH while sustaining the natural buffer capacity of the human skin surface. Graphical abstract